DESAIN MATERI BANGUN DATAR MENGGUNAKAN ORIGAMI BERKONTEKS TANGRAM DI SD KELAS II - Lisnani Lisnani (Suska Journal of mathematics Education, 2017)
ABSTRACT. The study aims to improve the ability of mathematical communication in recognizing, grouping various types of flat wake. The subjects of the study were elementary school students Class IIA in SD Negeri 43 Palembang amounted to 27 people. Data collection is done through observation sheets, interviews, tests, documentation, and field notes. The research method used is a research design consisting of three stages: First stage, preliminary design / preparing for the experiment; The second stage, design experiment consisting of pilot and teaching experiment. The third stage, retrospective analysis. This study develops a series of activities and strategies that learners do on a flat wake material. The results of this study in the form of learning trajectory (learning path) in each activity are: First activity, learners recognize various shapes and characteristics of wake up flat with conventional way. Then, on the second activity, learners can recognize the types and characteristics of the wake up trained by using the model match a make. Furthermore, the third activity, enhances its mathematical communication ability by using origang tangram context. Keywords : Design research, mathematical communication, make a match, origami